High-corrosion-resistance and high-strength stainless steel and manufacturing method thereof
By controlling the distribution of carbides and forming a martensite phase, high corrosion-resistant and high-strength stainless steel with ferrite and martensite duplex structures were prepared, which solved the problem that existing stainless steels were prone to cracks when increasing their strength, and achieved both high corrosion resistance and high strength.
Patent Information
- Application Number
- CN202380056638.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-04
- Filing Date
- 2023-03-10
- Publication Date
- 2025-03-11
AI Technical Summary
Existing ferritic stainless steels are prone to cracks or tear problems when increasing their strength, and conventional cold rolling processes are difficult to meet the requirements of high corrosion resistance and high strength at the same time.
High corrosion-resistant high-strength stainless steel with martensite and ferrite duplex structures were prepared by controlling the distribution of carbides and forming a martensite phase in the cold rolling annealing step. The specific method includes forming a martensite phase in the hot rolling annealing step and performing heat treatment during cold rolling annealing to induce a martensite phase transformation and solidly dissolving the carbide into the matrix.
It is achieved to ensure high strength and excellent molding quality of stainless steel without reducing corrosion resistance, and meet the needs of lightweight and high functionality.
Smart Images

Figure CN119604638A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a high-corrosion-resistant and high-strength stainless steel composed of a dual phase of martensite and ferrite after cold rolling and annealing heat treatment and a manufacturing method thereof. Background Art
[0002] Ferritic stainless steel products, which are widely used in various kitchen utensils, home appliances, and automotive parts, are increasingly required to have high functionality such as high strength and light weight. In particular, extreme cost savings are required, such as reducing thickness by increasing strength and improving energy efficiency by reducing weight. However, conventional ferritic stainless steel does not undergo phase transformation, so there are limitations to improving strength by grain refinement.
[0003] In order to solve this problem, a martensite phase is formed in the hot rolling annealing step to reduce the roughness that may be generated in the cold rolling process, thereby ensuring a cold-rolled steel sheet with a fine surface, but when the martensite phase is distributed in the hot rolling annealing step, the strength increases, so that cracks or steel sheet tearing may occur during the rolling process due to the rolling load during cold rolling. In order to solve this problem, the reduction rate per pass can be reduced during cold rolling, but this increases the number of passes and causes economic losses. A stainless steel that can ensure strength without reducing corrosion resistance is required. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] An object of the present invention to solve the above-mentioned problems is to provide a high corrosion-resistant and high-strength stainless steel in which the distribution of carbides is controlled and a martensite phase is formed in a cold rolling annealing step, and a method for producing the same.
[0006] However, the technical problems to be solved by the embodiments of the disclosed invention are not limited to the above-mentioned technical problems, and can be expanded in various ways within the scope of the technical ideas included in the present invention.
[0007] (II) Technical solution
[0008] The high corrosion-resistant and high-strength stainless steel according to one embodiment may contain, by weight%, C: 0.01-0.1%, N: 0.01-0.1%, Si: 0.01-1.0%, Mn: 0.01-3.0%, Cr: 10.0-20.0%, Al: 0.001-1.0%, P: 0.05% or less, S: 0.01% or less, the balance Fe and other inevitable impurities, and the distribution of carbides with a diameter of 0.5 μm or more may be 7 per unit area / 100 μm. 2 Hereinafter, the fine structure may be a dual phase of a martensite phase and a ferrite phase, and the area ratio of the martensite phase may be 20% or more.
[0009] The high corrosion resistant and high strength stainless steel according to one embodiment may satisfy the formula (1): 420C+470N+23Ni+10Mn+180-(11.5Cr+11.5Si+52Al)≥10. In the formula (1), C, N, Ni, Mn, Cr, Si and Al represent the weight % of each element.
[0010] The high corrosion-resistant and high-strength stainless steel according to one embodiment may have a pitting potential of 70 mV or more and a yield strength of 350 MPa or more.
[0011] The tensile strength of the high corrosion-resistant and high-strength stainless steel according to one embodiment may be 500 MPa or more.
[0012] The hardness of the high corrosion-resistant and high-strength stainless steel according to one embodiment may be 200 Hv or more.
[0013] The hardness of the martensite phase itself of the high corrosion-resistant and high-strength stainless steel according to one embodiment may be 400 Hv or more.
[0014] The aspect ratio of ferrite grains of the high corrosion-resistant and high-strength stainless steel according to one embodiment may be 2.0 or less.
[0015] The method for manufacturing high corrosion resistant and high strength stainless steel according to one embodiment may include the following steps: reheating a slab to 1050-1250° C., wherein the slab comprises, by weight%, C: 0.01-0.1%, N: 0.01-0.1%, Si: 0.01-1.0%, Mn: 0.01-3.0%, Cr: 10.0-20.0%, Al: 0.001-1.0%, P: 0.05% or less, S: 0.01% or less, the balance is Fe and other inevitable impurities; hot rolling and hot rolling annealing; cold rolling and cold rolling annealing at 950-1100°C, wherein the high corrosion resistant and high strength stainless steel satisfies the following formula (1): 420C+470N+23Ni+10Mn+180-(11.5Cr+11.5Si+52Al)≥10, and the microstructure is a dual phase of martensite phase and ferrite phase. In formula (1), C, N, Ni, Mn, Cr, Si and Al represent the weight % of each element.
[0016] In the method for producing high-corrosion-resistant and high-strength stainless steel according to one embodiment, the distribution of carbides having a diameter of 0.5 μm or more may be 7 per 100 μm per unit area. 2 the following.
[0017] In the method for manufacturing high corrosion-resistant and high-strength stainless steel according to one embodiment, the hot rolling annealing step may be performed at a temperature range of 750-900°C.
[0018] In the method for producing high corrosion-resistant and high-strength stainless steel according to one embodiment, the area ratio of the martensite phase after cold rolling and annealing may be 20% or more, and the hardness of the martensite phase after cold rolling and annealing may be 400 Hv or more.
[0019] In the method for producing the high corrosion-resistant and high-strength stainless steel according to one embodiment, the aspect ratio of the ferrite grains may be 2.0 or less.
[0020] (III) Beneficial effects
[0021] According to one embodiment of the present invention, a stainless steel having high corrosion resistance and high strength and a method for manufacturing the same can be provided, wherein the stainless steel has a dual phase of martensite and ferrite after cold rolling and annealing heat treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The photographs show the microstructures of comparative examples according to the cold rolling annealing temperature.
[0023] Figure 2 The photographs show the microstructures of the inventive examples according to the cold rolling annealing temperature.
[0024] Figure 3 The photographs show the microstructure and carbides of the comparative example according to the cold rolling annealing temperature.
[0025] Figure 4 The photographs show the microstructure and carbides of the inventive example according to the cold rolling annealing temperature. Best Mode for Carrying Out the Invention
[0026] The high corrosion-resistant and high-strength stainless steel according to one embodiment may contain, by weight%, C: 0.01-0.1%, N: 0.01-0.1%, Si: 0.01-1.0%, Mn: 0.01-3.0%, Cr: 10.0-20.0%, Al: 0.001-1.0%, P: 0.05% or less, S: 0.01% or less, the balance Fe and other inevitable impurities, and the distribution of carbides with a diameter of 0.5 μm or more may be 7 per unit area / 100 μm. 2 Hereinafter, the fine structure may be a dual phase of a martensite phase and a ferrite phase, and the area ratio of the martensite phase may be 20% or more. DETAILED DESCRIPTION
[0027] Below, the preferred embodiment of the present invention is described. However, the embodiment of the present invention can be modified into various other forms, and the technical idea of the present invention is not limited to the embodiment described below. In addition, the embodiment of the present invention is provided to more completely describe the present invention to those skilled in the art.
[0028] The terms used in this application are only used to illustrate specific examples. Therefore, unless the context clearly requires singularity, singular expressions include plural expressions. In addition, it should be noted that the terms "comprise", "include" or "have" used in this application are used to clearly indicate the existence of features, steps, functions, constituent elements or combinations thereof recorded in the specification, and are not used to preliminarily exclude the existence of other features or steps, functions, constituent elements or combinations thereof.
[0029] In addition, unless otherwise defined, all terms used in this specification should be considered to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. Therefore, unless clearly defined in this specification, specific terms should not be interpreted as overly idealized or formalized meanings.
[0030] In addition, the terms “approximately”, “substantially”, etc., are used in this specification to indicate the inherent manufacturing and material tolerances in the mentioned meaning with respect to the numerical value or a value close to the numerical value, and to prevent the disclosure of the exact or absolute numerical values used to aid the understanding of the present invention from being improperly exploited by unscrupulous infringers.
[0031] In the present invention, the stability of the austenite phase in the ferrite matrix is improved, and the cold rolling annealing heat treatment is performed at a temperature for generating the austenite phase so that the final product is composed of a dual phase of ferrite and martensite through martensitic transformation during cooling, thereby attempting to improve the strength according to the martensite fraction formed in the ferrite matrix. In addition, considering the load, cracks or fractures in the cold rolling step, hot rolling annealing is performed below Ac1, which is a ferrite single phase region, to form a soft ferrite single phase, and after the cold rolling is completed, heat treatment is performed at a temperature for generating the austenite phase in the cold rolling annealing step, thereby attempting to induce martensitic transformation during cooling to improve the strength.
[0032] In the cold rolling annealing step, heat treatment is performed at a temperature at which an austenite phase is generated, thereby removing the M precipitated on the ferrite phase. 23 C6 type carbides are dissolved in the matrix. According to the present invention, it is possible to provide a stainless steel and a method for producing the stainless steel, which can ensure high strength without deteriorating corrosion resistance by controlling the distribution of such carbides.
[0033] Furthermore, it is possible to provide a stainless steel and a method for manufacturing the stainless steel which does not reduce the molding quality of a final product by controlling the aspect ratio of ferrite grains.
[0034] In terms of weight %, the high corrosion resistant and high strength stainless steel according to one example of the present invention may contain: C: 0.01-0.1%, N: 0.01-0.1%, Si: 0.01-1.0%, Mn: 0.01-3.0%, Cr: 10.0-20.0%, Al: 0.001-1.0%, P: 0.05% or less, S: 0.01% or less, the balance Fe and other inevitable impurities. The reasons for limiting the alloy composition are described in detail below.
[0035] The content of C may be 0.01% to 0.1%.
[0036] C is an austenite stabilizing element, which has the effect of expanding the austenite phase region, thereby forming hard martensite during cooling and improving the strength of the steel. In order to obtain these effects, it is necessary to contain more than 0.01% C. In order to obtain the specified strength and fully expand the austenite region, it is preferably necessary to have more than 0.02% of the C. However, when the C content exceeds 0.1%, the steel plate becomes hardened, so that the ductility is significantly reduced, and when the amount of martensite generated is too much, formability cannot be obtained. In addition, when excessive addition of C generates a large amount of Cr carbides, the reduction of Cr leads to a decrease in corrosion resistance. Therefore, the C content is in the range of 0.01-0.1%. The C content can preferably be in the range of 0.02-0.1%.
[0037] The N content may be 0.01-0.1%.
[0038] Like C and Mn, N is an austenite stabilizing element and has the effect of expanding the austenite region. In order to obtain this effect, the N content needs to be 0.01% or more. However, when the N content exceeds 0.1%, due to the solid solution strengthening effect of N, the ductility decreases sharply, and the precipitation of Cr nitrides leads to a decrease in Cr, thereby reducing the corrosion resistance. Therefore, the N content is in the range of 0.01-0.1%. The N content can preferably be in the range of 0.02-0.1%, and more preferably in the range of 0.01-0.07%.
[0039] The content of Si may be 0.01-1.0%.
[0040] Si is an element that acts as a deoxidizer when steel is dissolved. In order to achieve this effect, it is necessary to contain more than 0.01% Si. However, when the Si content exceeds 1.0%, the steel plate becomes hardened, the rolling load during hot rolling increases, and surface defects such as sticking are also caused. In addition, Si is a ferrite stabilizing element, and excessive addition of Si reduces the stability of austenite. Therefore, the Si content is in the range of 0.01-1.0%. The Si content can preferably be in the range of 0.20-0.50%.
[0041] The content of Mn may be 0.01-3.0%.
[0042] Like C, Mn is an austenite phase stabilizing element and has the effect of expanding the austenite phase region. In order to obtain this effect, it is necessary to contain 0.01% or more of Mn. However, when the content of Mn exceeds 3.0%, the amount of MnS generated increases, thereby reducing corrosion resistance. Therefore, the content of Mn is in the range of 0.01-3.0%. The content of Mn can preferably be 0.2-1.0%.
[0043] The content of Cr may be 10.0-20.0%.
[0044] Cr is an element that has the effect of improving corrosion resistance by forming a passive film on the surface of the steel plate. This effect occurs when the Cr content is 10.0% or more, and as the Cr content increases, the corrosion resistance improves. In addition, Cr is a ferrite stabilizing element and has the effect of inhibiting the formation of an austenite phase. When the Cr content is less than 10.0%, too much austenite phase is generated, and the specified formability cannot be obtained. Therefore, the Cr content is 10.0% or more. However, when the Cr content exceeds 20.0%, the austenite phase cannot be generated, and the required fraction of the martensite phase cannot be ensured. Therefore, the Cr content is in the range of 10.0-20.0%. The Cr content can preferably be in the range of 12.0-18.0%.
[0045] The content of Al may be 0.001-1.0%.
[0046] Like Si, Al is an element that acts as a deoxidizer. In order to obtain this effect, it is necessary to contain more than 0.001% Al. However, when the Al content exceeds 1.0%, Al inclusions such as Al2O3 increase, so the surface properties tend to deteriorate. Therefore, the Al content is in the range of 0.001-1.0%. The Al content can preferably be in the range of 0.001-0.1%.
[0047] The content of Ni may be 0.01% to 1.0%.
[0048] Ni is a representative austenite stabilizing element, but Ni is an expensive element and increases manufacturing costs. In addition, although Ni has the effect of improving corrosion resistance, when added in large quantities, the impurities of the material increase and there is a problem of reduced elongation. Therefore, in the present invention, 0.01-1.0% Ni may be optionally included. The content of Ni may preferably be 0.5% or less.
[0049] The P content may be 0.05% or less.
[0050] P is an element that promotes grain boundary destruction through grain boundary segregation, and therefore is an unavoidable impurity, and the content of P is preferably as low as possible. Therefore, the content of P is 0.05% or less. The content of P is more preferably 0.03% or less.
[0051] The S content may be 0.01% or less.
[0052] S is an element that reduces ductility and corrosion resistance by forming sulfide-based inclusions such as MnS. In particular, when the content of S exceeds 0.01%, its adverse effects are significantly produced. Therefore, S is an unavoidable impurity, and the content of S is preferably as low as possible. Therefore, the content of S is 0.01% or less. The content of S is more preferably 0.005% or less.
[0053] The balance is iron (Fe). However, in the conventional manufacturing process, undesirable impurities may inevitably be mixed in from the raw materials or the surrounding environment, so these impurities cannot be eliminated. These impurities are well known to technicians in the conventional manufacturing process, so all of them are not specifically described in this specification.
[0054] Hereinafter, a highly corrosion-resistant and high-strength stainless steel according to one embodiment of the present invention having the above-mentioned alloy composition will be described.
[0055] The distribution of carbides with a diameter of 0.5 μm or more in the high corrosion resistant and high strength stainless steel according to one embodiment of the present invention may be 7 / 100 μm per unit area. 2 When the distribution of carbides exceeds 7 / 100μm per unit area 2 When the corrosion resistance and high strength are not achieved at the same time.
[0056] In the high corrosion resistant and high strength stainless steel according to an example of the present invention, the microstructure is a dual phase of a martensite phase and a ferrite phase, wherein the area ratio of the martensite phase may be greater than 20%. When the area ratio of the martensite phase is less than 20%, high strength may not be ensured.
[0057] In the high corrosion resistant and high strength stainless steel according to one embodiment of the present invention, carbides are dissolved in the matrix, so that when the distribution of carbides with a diameter of 0.5 μm or more is 7 per unit area / 100 μm 2 When the ratio is below 0.1, the reduction in corrosion resistance caused by the precipitation of carbides can be prevented, and high strength can be ensured by ensuring that the area ratio of the martensite phase is more than 20%. Therefore, the high corrosion-resistant and high-strength stainless steel can be a stainless steel that satisfies both high corrosion resistance and high strength.
[0058] The value of the formula (1) of the high corrosion-resistant and high-strength stainless steel according to one example of the present invention may be 10 or more.
[0059] Formula (1): 420C+470N+23Ni+10Mn+180-(11.5Cr+11.5Si+52Al)
[0060] In formula (1), C, N, Ni, Mn, Cr, Si and Al represent the weight % of each element.
[0061] When the value of formula (1) is less than 10, the stability of the austenite phase is low, and the phase transformation of the austenite phase may not actively occur, so the phase transformation into martensite may not be possible. Therefore, the value of the formula (1) is controlled to be 10 or more, preferably 30 or more. Therefore, after the austenite phase is formed at a high temperature, the martensite phase transformation can be smoothly carried out during the cooling process, so that the area ratio of the martensite phase can be ensured to be 20% or more.
[0062] The high corrosion-resistant and high-strength stainless steel according to an example of the present invention has a pitting potential of 70 mV or more and a yield strength of 350 MPa or more, and thus can satisfy both corrosion resistance and strength.
[0063] In addition, the tensile strength of the high corrosion resistant and high strength stainless steel according to an example of the present invention may be 500 MPa or more, the hardness of the steel may be 200 Hv or more, and the hardness of the martensite phase may be 400 Hv or more.
[0064] In addition, the aspect ratio of the ferrite grains of the high corrosion resistant and high strength stainless steel according to one example of the present invention can be less than 2.0. The aspect ratio of the ferrite grains refers to the ratio of the length of the ferrite grains in the rolling direction divided by the length of the ferrite grains in the thickness direction. In the present invention, the aspect ratio of the ferrite grains is represented by formula (2).
[0065] Formula (2): Ar = Dr / Dt
[0066] Here, Ar refers to the aspect ratio of the ferrite grains, Dr refers to the length of the ferrite grains in the rolling direction, and Dt refers to the length of the ferrite grains in the thickness direction.
[0067] The ferrite grains show a level of about 30-50 μm, and when the non-recrystallized ferrite grains elongated in the rolling direction are distributed, the possibility of deterioration of the forming quality such as wrinkling is high. Therefore, the ferrite phase that does not undergo phase transformation is preferably distributed in the form of equiaxed recrystallized grains as much as possible to prevent the forming quality of the final product from being reduced. Therefore, the present invention can also obtain excellent forming quality by controlling the aspect ratio of the ferrite grains to 2.0 or less.
[0068] Hereinafter, a method for producing the high corrosion-resistant and high-strength stainless steel having the above-mentioned alloy composition according to one embodiment of the present invention will be described.
[0069] The high corrosion-resistant and high-strength stainless steel of the present invention can be produced by subjecting a slab having the above alloy composition to a process of reheating-hot rolling-finish rolling-hot rolling annealing-cold rolling-cold rolling annealing.
[0070] The manufacturing method of the high corrosion-resistant and high-strength stainless steel of the present invention may include the following steps: reheating a slab, wherein the slab contains, by weight%, C: 0.01-0.1%, N: 0.01-0.1%, Si: 0.01-1.0%, Mn: 0.01-3.0%, Cr: 10.0-20.0%, Al: 0.001-1.0%, P: less than 0.05%, S: less than 0.01%, the remainder of Fe and other inevitable impurities; hot rolling and hot rolling annealing; cold rolling and cold rolling annealing.
[0071] The value of the formula (1) of the slab having the above alloy composition may be 10 or more.
[0072] Formula (1): 420C+470N+23Ni+10Mn+180-(11.5Cr+11.5Si+52Al)
[0073] In formula (1), C, N, Ni, Mn, Cr, Si and Al represent the weight % of each element.
[0074] When the value of formula (1) is less than 10, the stability of the austenite phase is low, and the phase transformation of the austenite phase may not actively occur, so the phase transformation to martensite may not occur. Therefore, the value of the formula (1) is controlled to be 10 or more, preferably 30 or more, so that after the austenite phase is formed at a high temperature, the martensite phase transformation can be smoothly carried out during the cooling process.
[0075] The slab having the above alloy composition may be reheated to 1050-1250°C and hot rolled. The finishing rolling temperature may be set to 700-950°C.
[0076] In addition, hot rolling annealing may be performed at 750° C. to 900° C., which is below the Ac1 temperature of the ferrite single phase region. More preferably, hot rolling annealing heat treatment may be performed at 800° C. to 850° C. to form a soft ferrite single phase.
[0077] The hot rolled sheet composed of a soft ferrite single phase can be cold rolled at room temperature. Cold rolling annealing can be performed after cold rolling. Cold rolling annealing can be performed at 950-1100°C. Heat treatment is performed at a temperature above 950°C, which is a temperature above 900°C for generating an austenite phase, so as to induce martensitic transformation during the cooling process, thereby improving strength. However, when annealing is performed at a temperature exceeding 1100°C, the coarsening of ferrite grains leads to reduced formability, or in severe bending processing parts, the orange peel phenomenon caused by the coarsening of grains may occur on the surface of the bent part, so it is preferred to perform heat treatment at a temperature below 1100°C.
[0078] In addition, in the method for producing high corrosion resistant and high strength stainless steel of the present invention, the cold rolling annealing temperature is heat treated at a temperature at which an austenite phase is generated, so that the M precipitated on the ferrite phase can be 23 C6 type carbides are solid-dissolved in the matrix.
[0079] In the method for manufacturing high corrosion resistant and high strength stainless steel of the present invention, cold rolling and annealing heat treatment is performed at a temperature for generating an austenite phase, so that carbides are dissolved in the matrix, and the distribution of carbides with a diameter of 0.5 μm or more can be 7 per 100 μm per unit area. 2 the following.
[0080] In the method for manufacturing high corrosion resistant and high strength stainless steel of the present invention, the hardness of the martensite phase after cold rolling and annealing can be above 400 Hv. The carbon decomposed in the carbide improves the stability of the austenite phase, thereby forming an austenite phase, and a high hardness martensite phase of a BCT structure can be formed during cooling.
[0081] In the manufacturing method of the high corrosion resistant and high strength stainless steel of the present invention, the area ratio of the martensite phase after cold rolling and annealing can be 20% or more. When the cold rolling and annealing heat treatment is performed at a temperature at which the austenite phase is generated, the area ratio of the martensite phase increases as the temperature rises, thereby improving the yield strength and tensile strength.
[0082] When carbides are dissolved in the matrix and the distribution of carbides with a diameter of 0.5 μm or more is 7 per 100 μm per unit area 2 When the MgO ratio is less than 1.5, a decrease in corrosion resistance due to carbide precipitation can be prevented, and a martensite phase having high hardness can be generated. The area ratio of the martensite phase is increased, and strength can be ensured.
[0083] The stainless steel manufactured by the method for manufacturing high-corrosion-resistant and high-strength stainless steel according to one example of the present invention has a pitting potential of 70 mV or more and a yield strength of 350 MPa or more, and thus can satisfy both corrosion resistance and strength.
[0084] Furthermore, the tensile strength of the stainless steel manufactured by the method for manufacturing high corrosion-resistant and high-strength stainless steel according to one example of the present invention can be 500 MPa or more, and the hardness of the steel can be 200 Hv or more.
[0085] In addition, the aspect ratio of the ferrite grains represented by formula (2) of the stainless steel manufactured by the manufacturing method of high corrosion resistant and high strength stainless steel according to one example of the present invention satisfies 2.0 or less, thereby improving the molding quality of the final product. Formula (2) is Ar=Dr / Dt, wherein Ar refers to the aspect ratio of the ferrite grains, Dr refers to the length of the ferrite grains in the rolling direction, and Dt refers to the length of the ferrite grains in the thickness direction.
[0086] Hereinafter, the present invention will be described in more detail by way of examples. However, the description of these examples is only used to illustrate the implementation of the present invention, and the present invention is not limited by these examples. This is because the scope of the present invention is determined by the matters described in the claims and the matters reasonably derived therefrom.
[0087] {Example}
[0088] The slab is subjected to a process of reheating-hot rolling-finishing rolling-hot rolling annealing-cold rolling-cold rolling annealing within the temperature range of the present invention to produce a cold rolling annealing material, wherein the slab contains, by weight%, C: 0.035%, N: 0.038%, Si: 0.32%, Mn: 0.5%, Cr: 16.3%, Al: 0.003%, Ni: 0.09%, P: 0.02% or less, S: 0.004% or less, and the balance of Fe and other inevitable impurities. In particular, in order to confirm the effect of the cold rolling annealing heat treatment temperature according to the present invention, the production is carried out within the scope of the present invention, but the cold rolling annealing heat treatment temperature is changed as shown in Table 1 below.
[0089] Table 1 below shows the fraction of the martensite phase of Examples according to the cold rolling annealing heat treatment temperature.
[0090] [Table 1]
[0091]
[0092] Figure 1 and Figure 2 is a photograph showing the microstructure of the embodiment according to the cold rolling annealing heat treatment temperature. The change of the microstructure was observed using a SEM electron microscope. It can be confirmed that Comparative Examples 1 to Comparative Examples 4 are composed of a ferrite phase. In Inventive Examples 1 to Inventive Examples 4, Figure 2 The white phase part in the middle corresponds to the ferrite phase, and the black phase part corresponds to the martensite phase. Figure 1 and Figure 2 It can be confirmed that the fraction of the martensite phase in the ferrite matrix increases as the cold rolling annealing heat treatment temperature increases.
[0093] Comparative Examples 1 to 4, in which the cold rolling annealing heat treatment temperature is not within the scope of the present invention, consist only of a ferrite phase, and as the temperature rises, a martensite phase may exist, but only in a trace amount that cannot be measured. On the contrary, in Inventive Examples 1 to 4, which correspond to the scope of the present invention, the cold rolling annealing heat treatment temperature is equivalent to 950° C. or more, so that it can be confirmed that the fraction of the martensite phase in the ferrite matrix can be ensured to be 20% or more.
[0094] Table 2 below shows the M per unit area according to the cold rolling annealing heat treatment temperature. 23 The number of C6 type carbides.
[0095] [Table 2]
[0096]
[0097] Figure 3 and Figure 4 The microstructure and M of the embodiment according to the cold rolling annealing heat treatment temperature are shown in FIG. 23 The number of C6 carbides (pcs / 100μm 2 ). The changes in microstructure and carbides were observed using a SEM electron microscope. Figure 3 and Figure 4 In FIG. 1 , the martensite phase is represented by M, and the ferrite phase is represented by F. As in Comparative Examples 1 and 3, when the hot rolling annealing temperature is lower than 950° C., it can be confirmed that a large amount of carbides exist.
[0098] pass Figure 4 It can be confirmed that the martensite phase is generated at a temperature above 950°C, and it can be confirmed that the carbides are dissolved and their distribution gradually decreases. Figure 3 and Figure 4 It was confirmed that as the cold rolling annealing heat treatment temperature increased, the fraction of the martensite phase in the ferrite matrix increased and the number of carbides per unit area decreased.
[0099] In the comparative example where the cold rolling annealing heat treatment temperature is not within the scope of the present invention, it can be confirmed that the number of carbides per unit area exceeds 7. On the contrary, in the inventive example corresponding to the scope of the present invention, the cold rolling annealing heat treatment temperature is equivalent to 950° C. or more, so that it can be confirmed that the number of carbides per unit area is reduced to 7 or less.
[0100] Table 3 below shows the pitting potential, yield strength, tensile strength, elongation and hardness of the examples.
[0101] [Table 3]
[0102]
[0103] As shown in Table 3, when the cold rolling annealing heat treatment temperature of the present invention is met and the area fraction of the martensite phase is 20% or more, and the number of carbides per unit area is 7 or less, the pitting potential is 70 mV or more and the yield strength is 350 MPa or more, thereby ensuring that the stainless steel can prevent the reduction of corrosion resistance while meeting the high strength requirement. The pitting potential was measured at 0.333 mV / second in a 3.5% NaCl solution at a temperature of 30°C.
[0104] In Comparative Examples 2 to 4, in which the cold rolling annealing temperature was increased and a very small amount of martensite began to be generated, it can be seen that the yield strength and tensile strength increased compared to Comparative Example 1. In Inventive Examples 1 to 4, which were performed at a cold rolling annealing temperature above the range corresponding to the present invention, it can be confirmed that the martensite fraction increased to 20% or more, so the yield strength was 350 MPa or more and the tensile strength was 500 MPa or more, thereby ensuring excellent strength.
[0105] In addition, in the case of Invention Examples 1 to 4 where the cold rolling annealing temperature is equivalent to 950°C or higher, which is equivalent to the temperature at which carbides are dissolved, the number of carbides per unit area in the ferrite matrix is 7 or less, and it can be confirmed that the reduction in pitting potential value caused by consumption of Cr due to precipitation of carbides can be prevented. Therefore, it can be confirmed that excellent corrosion resistance with a pitting potential of 70 mV or higher can be ensured.
[0106] In the case of Comparative Examples 2 to 4, the pitting potential value is less than 70 mV. This corresponds to the cold rolling annealing temperature being a temperature at which carbides are not dissolved but precipitated. Therefore, Cr is consumed by the precipitation of carbides, and the pitting potential is reduced.
[0107] However, in the case of Comparative Example 1, it was confirmed that the pitting potential value was equivalent to 70 mV or more, but the yield strength was low, and even if the corrosion resistance was ensured, the strength could not be ensured.
[0108] In addition, the hardness of the steel is expressed as the average value of 10 measurements with a micro Vickers hardness meter at a load of 1 kg. In the case of Comparative Examples 1 to 4 in which there is no martensite phase, it can be confirmed that the hardness value is measured to be about 140 Hv, and the hardness is poor. On the contrary, in the case of Inventive Examples 1 to 4 in which there is more than 20% of the martensite phase, the hardness value is measured to be more than 200 Hv, and it can be confirmed that high hardness is obtained.
[0109] The present invention can provide a stainless steel which is subjected to cold rolling annealing heat treatment within a temperature range which is equivalent to the temperature at which carbides are dissolved in solid solution and which is equivalent to the temperature at which a phase transformation to a martensite phase and generation of an austenite phase occurs during the cold rolling annealing process after the completion of cold rolling, thereby inducing a phase transformation to a martensite phase during the cooling process, thereby controlling the number of carbides per unit area to less than 7, ensuring that the fraction of the martensite phase is more than 20%, thereby satisfying both corrosion resistance and strength.
[0110] Table 4 below shows the hardness values of the martensite phase and the ferrite phase themselves.
[0111] [Table 4]
[0112]
[0113] The hardness of the martensite phase and the ferrite phase itself is equivalent to the value measured by a microhardness tester (load: 5g). It can be confirmed that the hardness of the ferrite phase of the invention example itself is about 150-160Hv, the same as the comparative example, and the hardness of the martensite phase itself is 400Hv or more, which is a high hardness value. That is, in terms of the hardness of the steel of the invention example itself, the M precipitated on the ferrite phase by performing cold rolling annealing heat treatment in the austenite region is 23 C6 type carbides are dissolved in the matrix. At this time, the carbon decomposed from the carbides improves the stability of the austenite phase to form an austenite phase, and forms a high-hardness martensite phase with a BCT structure during cooling, thereby achieving high hardness.
[0114] Table 5 below shows the aspect ratios of ferrite grains.
[0115] [Table 5]
[0116]
[0117] The aspect ratio of the ferrite grains according to one example of the present invention may be 2.0 or less. The aspect ratio of the ferrite grains refers to the ratio of the length of the ferrite grains in the rolling direction divided by the length of the ferrite grains in the thickness direction. In the present invention, it is represented by formula (2) and represented by Ar=Dr / Dt. Wherein, Ar refers to the aspect ratio of the ferrite grains, Dr refers to the length of the ferrite grains in the rolling direction, and Dt refers to the length of the ferrite grains in the thickness direction. In the present invention, in order to confirm the aspect ratio of the ferrite grains, the cross-sectional thickness direction of the steel plate in the rolling direction is divided into a total of 5 regions from the upper surface layer to the bottom surface layer on the other side, and then the aspect ratios of 1000 ferrite grains are measured in each of the 5 regions and the average value in each region is calculated, and the average value is calculated to calculate the aspect ratio of the entire region. It is set to the aspect ratio of the ferrite grains, and it can be controlled to be less than 2.0. In one example of the present invention, it was confirmed that the reduction in molding quality can be prevented by controlling the aspect ratio of ferrite grains to 2.0 or less.
[0118] Finally, the present invention controls the reheating temperature, finishing rolling temperature, hot rolling annealing temperature, and cold rolling annealing temperature of the stainless steel forming the austenite phase, and especially performs cold rolling annealing heat treatment at above 950°C to generate the austenite phase, thereby inducing martensitic phase transformation during the cooling process and inducing solid solution of carbides, ensuring that the fraction of the martensitic phase is above 20%, and controlling the number of carbides per unit area to less than 7. Therefore, it can be confirmed that a stainless steel and a method for manufacturing the same can be provided that can ensure both corrosion resistance and strength.
[0119] It was confirmed that it is possible to provide a stainless steel having a pitting potential of 70 mV or more, having good corrosion resistance and excellent yield strength, tensile strength and hardness, and a method for producing the same, thereby simultaneously satisfying high corrosion resistance and high strength.
[0120] Furthermore, it was confirmed that by controlling the aspect ratio of ferrite grains to 2.0 or less, an effect of preventing a decrease in forming quality can also be obtained.
[0121] As described above, exemplary embodiments of the present invention have been described, but the present invention is not limited thereto, and those skilled in the art will appreciate that various changes and modifications may be made without departing from the concept and scope of the claims.
[0122] Industrial Applicability
[0123] According to one embodiment of the present invention, a stainless steel having a dual phase of martensite and ferrite after cold rolling and annealing heat treatment and satisfying high corrosion resistance and high strength and a method for manufacturing the stainless steel can be provided, thus having industrial applicability.
Claims
1. A high corrosion resistant and high strength stainless steel, which comprises, by weight%, C: 0.01-0.1%, N: 0.01-0.1%, Si: 0.01-1.0%, Mn: 0.01-3.0%, Cr: 10.0-20.0%, Al: 0.001-1.0%, P: 0.05% or less, S: 0.01% or less, and the balance of Fe and other inevitable impurities, in, The distribution of carbides with a diameter of 0.5 μm or more is 7 / 100 μm per unit area. 2 the following, The microstructure is a dual phase of martensite and ferrite. The area ratio of the martensite phase is 20% or more.
2. The high corrosion-resistant and high-strength stainless steel according to claim 1, wherein: The high corrosion resistant and high strength stainless steel satisfies the following formula (1): Formula (1): 420C+470N+23Ni+10Mn+180-(11.5Cr+11.5Si+52Al)≥10 In formula (1), C, N, Ni, Mn, Cr, Si and Al represent the weight % of each element.
3. The high corrosion-resistant and high-strength stainless steel according to claim 1, wherein: The high corrosion-resistant and high-strength stainless steel has a pitting potential of 70 mV or more and a yield strength of 350 MPa or more.
4. The high corrosion-resistant and high-strength stainless steel according to claim 1, wherein: The tensile strength of the high corrosion-resistant and high-strength stainless steel is above 500 MPa.
5. The high corrosion-resistant and high-strength stainless steel according to claim 1, wherein: The hardness of the high corrosion-resistant and high-strength stainless steel is above 200 Hv.
6. The high corrosion-resistant and high-strength stainless steel according to claim 1, wherein: The hardness of the martensite phase is 400 Hv or more.
7. The high corrosion-resistant and high-strength stainless steel according to claim 1, wherein: The aspect ratio of ferrite grains is 2.0 or less.
8. A method for manufacturing high corrosion resistant and high strength stainless steel, comprising the following steps: The slab is reheated to 1050-1250° C., and the slab contains, by weight%, C: 0.01-0.1%, N: 0.01-0.1%, Si: 0.01-1.0%, Mn: 0.01-3.0%, Cr: 10.0-20.0%, Al: 0.001-1.0%, P: less than 0.05%, S: 0.01% or less, the balance is Fe and other unavoidable impurities; hot rolling and hot rolling annealing; and Cold rolling and cold annealing at 950-1100℃, The high corrosion-resistant and high-strength stainless steel satisfies the following formula (1), and the microstructure is a dual phase of martensite and ferrite. Formula (1): 420C+470N+23Ni+10Mn+180-(11.5Cr+11.5Si+52Al)≥10 In formula (1), C, N, Ni, Mn, Cr, Si and Al represent the weight % of each element.
9. The method for producing high corrosion resistant and high strength stainless steel according to claim 8, wherein: The distribution of carbides with a diameter of 0.5 μm or more is 7 / 100 μm per unit area. 2 the following.
10. The method for producing high corrosion resistant and high strength stainless steel according to claim 8, wherein: The hot rolling annealing step is performed at 750-900°C.
11. The method for producing high corrosion resistant and high strength stainless steel according to claim 8, wherein: After the cold rolling and annealing, the area ratio of the martensite phase is greater than 20%.
12. The method for producing high corrosion resistant and high strength stainless steel according to claim 8, wherein: The hardness of the martensite phase after the cold rolling annealing is greater than 400 Hv.
13. The method for producing high corrosion resistant and high strength stainless steel according to claim 8, wherein: The aspect ratio of ferrite grains is 2.0 or less.